The influence of intellectual capital on company value with financial performance as an intervening variable in financing institutions in Indonesia - Susi Nafiroh; Joicenda Nahumury (STIE Perbanas Surabaya, 2016)
The objective of this study is to examine the influence of intellectual capital on compa-ny value with financial performance as an intervening variable in financing institu-tions listed on the Indonesian Stock Exchange (IDX) 2010 - 2014. This research uses Value Added Intellectual Coefficient (VAICTM) model that consists of three compo-nents: Value Added Capital Employed (VACA), Value Added Human Capital (VA-HU), and Value Added Structural Capital (STVA). Company value is measured using Tobin’s Q, financial performance is measured using Return on Asset (ROA), Return on Equity (ROE), and Earning per Share (EPS). The data consisted of 67 samples. Sampling is conducted using census method. Data analysis technique used in this study is Partial Least Square (PLS). The results show that: (1) intellectual capital has an influence on company value (2) financial performance mediates the relationship between intellectual capital and company value. The important thing in this study is that intellectual capital can be used for adding the firm value.